Swarm intelligence optimization algorithms: a review - Odili, Julius Beneoluchi; M. N. M., Kahar; Noraziah, Ahmad (UTeM, 2018)
Swarm Intelligence, of late, has gradually become an exciting area of research interest to many researchers in science and engineering. The primary reason for this interest is because swarm intelligence exploits the miraculous cum harmonious working of nature in ensuring order, preservation, conservation, longevity and sustenance of plants and animals in the ecosystem. As a result, researchers that believe that mimicking nature is key to solving diverse problems in engineering, technology and science has developed a number of swarm intelligence techniques. This paper presents a review of some recently developed swarm intelligence algorithms that have been successfully applied to solve a number of optimization problems with special emphasis on their application areas, strengths and observable weaknesses. This study aims to assist researchers in their choice of algorithm to solve optimization problems.